Insights into Fischer–Tropsch catalysis: current perspectives, mechanisms, and emerging trends in energy research - Keunecke, Arthur; Dossow, Marcel; Dieterich, Vincent; Spliethoff, Hartmut; Fendt, Sebastian (Frontiers in Energy Research, 2024)
Fischer–Tropsch (FT) synthesis is an important module for the production of clean and sustainable fuels and chemicals, making it a topic of considerable interest in energy research. This mini-review covers the current literature on FT catalysis and offers insights into the primary products, the nuances of the FT reaction, and the product distribution, with particular attention to the Anderson–Schulz–Flory distribution (ASFD) and known deviations from this fundamental concept. Conventional FT catalysts, particularly Fe- and Co-based catalysis systems, are reviewed, highlighting their central role and the influence of water and water–gas shift (WGS) activity on their catalytic behavior. Various mechanisms of catalyst deactivation are also investigated, and the high methanation activity of Co-based catalysts is illustrated. To make this complex field accessible to a broader audience, we explain conjectured reaction mechanisms, namely, the carbide mechanism and CO insertion. We discuss the complex formation of a wide range of products, including olefins, kerosenes, branched hydrocarbons, and by-products such as alcohols and oxygenates. The article goes beyond the traditional scope of FT catalysis by addressing topics of current interest, including the direct hydrogenation of CO2 for power-to-X applications and the use of bifunctional catalysts to produce tailored FT products, most notably for the production of sustainable aviation fuel (SAF). This mini-review provides a holistic overview of the evolving landscape of FT catalysts and is aimed at both experienced researchers and those new to the field while covering current and emerging trends in this important area of energy research.